Zespoły maskujące złośliwe zapalenia błony naczyniowej - Kubicka-Trząska, Agnieszka; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
The term “Masquerade Syndrome” was first used in ophthalmology in 1967 by Theodore, to describe a case of conjunctival carcinoma that manifested as chronic conjunctivitis. The Uveitis Masquerade Syndromes (UMS) are a group of various ocular diseases that may mimic chronic intraocular inflammation. Many malignant pathologies may result in an appearance masquerading as uveitis. The article reviews most common malignant conditions which may be considered masquerades such as primary intraocular lymphoma, leukemias, uveal melanoma, retinoblastoma, metastatic lesions, and paraneoplastic syndromes, among others. Diagnostic strategies, therapies, and prognosis are also reviewed.